Labor Stress and Its Influence in the Performance of Workers - Zuñiga Cristobal, Evelyn Carina (2019)
Stress has a direct relationship with work performance, and other variables; according to the diverse investigations carried out and theoretical bases studied on the subject. Work-related stress is an increasingly frequent problem, however, although there are programs to treat and prevent it, it has not diminished, according to statistics. Many experts have tried to define work stress, but the most complete concept is the World Health Organization (WHO, 2004) that defines a variable, such as: “the physiological, psychological and behavioral response of an individual trying to control and adjust to internal and external pressures. Work stress appears when there is a mismatch between the person, the job and the organization itself.” (p.4). The globalization and instability that organizations are going through in these years, makes workers feel frustrated and thereby become emotionally stressed; and this in turn leads to an increase in work stress levels and therefore a low work performance. For this reason, the evaluation for investigating the variable work stress and performance has increased today. In this reflection, a lot of information on this problem has been reviewed, in order to offer an overview and updated of both variables. Likewise, we will show the main approaches, concepts of work stress and their relation to work performance, what are the causes and some prevention proposals for their control.